Elevated PAPP-A levels in lean patients with polycystic ovary syndrome - Merve Öztürk; Mesut Öktem; S. Özlem Altinkaya; Emel Özalp Öktem; Şehri Elbeg; Ahmet Erdem; Mehmet Erdem (Elsevier, 2018)
Objectives: This study aimed to evaluate the serum concentrations of PAPP-A (pregnancy associated placental protein-A), a biomarker which is associated with cardiovascular disease, in patients with polycystic ovary syndrome (PCOS). Materials and Methods: A total of 62 women with PCOS, and 68 age and body mass index (BMI) matched controls were eligible for the study. Hirsutism scores, hormonal and metabolic profile as well as PAPP-A levels were assessed in each subject. Results: Women with PCOS and controls yielded similar median serum levels of PAPP-A (1.7 ng/ml versus 1.8 ng/ml, respectively, p = 0.328). However, when patients were compared based on BMI; subgroup analyses found that among women with BMI<27 kg/m2, patients with PCOS exhibited higher PAPP-A levels than controls (2.1 ng/ml versus 1.8 ng/ml, respectively, p = 0.018). When women with PCOS were evaluated in their own based on BMI, lean PCOS women showed higher levels of PAPP-A (2.1 ng/ml versus 1.5 ng/ml, p = 0.002). PAPP-A levels were negatively correlated with age (p = 0.031, r = −0.189), BMI (p = 0.002, r = −0.265) and triglyceride levels (p < 0.001, r = −0.3). Conclusion: The data of the present study suggested that PAPP-A might be a clinical indicator in PCOS, in which the risks of metabolic syndrome and cardiovascular event are increased. Especially a group of young patients with BMI <27 kg/m2 might benefit from the cardiovascular risk evaluation using PAPP-A, supplying prognostic information for high risk in the development of cardiovascular disease.